THE ROLE OF ARTIFICIAL INTELLIGENCE IN LIBRARY MANAGEMENT SYSTEMS - Zahida Henez (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Among the many industries seeing rapid AI transformation are library management systems (LMS). Streamlining processes, improving the user experience, and enhancing resource management are the goals of integrating AI technologies into LMS. how artificial intelligence (AI) might improve library operations by automating cataloguing, indexing, and retrieval of resources. Powerful search capabilities, tailored suggestions, and quick data retrieval are all made possible by AI-driven technologies like natural language processing and machine learning algorithms. Furthermore, AI improves inventory control and collection management through predictive analytics, which in turn enhances decision-making. Concerns about data protection, the necessity to train staff, and the integration of AI with conventional library procedures are just a few of the potential and threats connected with deploying AI in library systems. When it comes to building more efficient, user-centered, and scalable library environments, AI plays a crucial role in library management systems.